TINGKAT PENGETAHUAN ORTODONTIK DENGAN KEPATUHAN KONTROL PASIEN ORTODONTIK CEKAT DI KLINIK BRIGHT DENTAL CARE YOGYAKARTA - Susanti Widhiastutiningsih; Sri Ediati; Almujadi Almujadi (Journal of Oral Health Care, 2015)
Background:Knowledge is the result of know and this occursafter someone is doing the sensing of the particularobjec. Compliance is a condition that is created and formedthrough a process of a series of behaviors that demonstratevalue - the value of obedience, obedience, loyalty,regularity and order. Orthodontic treatment aims to set theteeth into the correct position.Objective:To determine the relationship of the level ofknowledge of orthodontic premises fixed orthodontic patientcompliance controls at Bright Dental Care clinic,Yogyakarta.Methods:Cross sectional analytic survey sampling quotasampling technique with a criterion of patients wearingfixed orthodontic appliance maxilla and mandible, femaleor male - male, aged 15-40 years and 30 respondents.Research variables consists of variables that influencethe level of knowledge orthodontic ordinal scale assessmentand compliance control variables is affected by anominal scale assessment. Test data analysis using theKruskal-Wallis test correlation.Results:High level of orthodontic knowledge as much as26 percent of respondents with 86.7%, a total of 24 respondentsdutifully control the percentage of respondentswith 80%. Has a high level of knowledge of orthodonticcompliance controls as much as 23 percent of respondentswith 76.7%. Correlation coefficient with p = 0.004showed sig < 0.05 Ho rejected it means that there is arelationship between the level of knowledge of orthodonticpatients with fixed orthodontic compliance controls at BrightDental Care clinic, Yogyakarta.Conclusion:There is a relationship between the level ofknowledge of orthodontic patients with fixed orthodonticcompliance controls at Bright Dental Care clinic,Yogyakarta